2012
DOI: 10.1108/01443571211223103
|View full text |Cite
|
Sign up to set email alerts
|

Service specialization and operational performance in hospitals

Abstract: PurposeThe purpose of this paper is to examine the link between service specialization and operational performance in hospitals. Existing literature has mostly been concerned with the performance effects of operational focus, which can be seen as an extreme form of specialization. It is not clear, however, whether an effect similar to the focus effect can be observed also in cases where specialization takes on less extreme forms. The authors analyze this effect up to and above the effects of volume, learning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 57 publications
4
48
1
Order By: Relevance
“…In line with previous studies, [39] this finding indicates that a reduction in ALOS improves hospital performance. Although thresholds of ALOS vary with different kinds of treatments, it will require a new study to address such variations as the data used here is aggregated at the hospital level.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In line with previous studies, [39] this finding indicates that a reduction in ALOS improves hospital performance. Although thresholds of ALOS vary with different kinds of treatments, it will require a new study to address such variations as the data used here is aggregated at the hospital level.…”
Section: Discussionsupporting
confidence: 82%
“…Model ( [29,39] this exercise went further to analyze the statistical impact of ALOS and BTR, on BOR controlling for BED, ADM, and PD.…”
Section: Model (I)mentioning
confidence: 99%
“…Both Atella et al and Herwartz and Strumann, conversely, found a negative relationship between the Gini index and hospital efficiency, the former among 1233 Italian hospitals for the years 1999‐2007, the latter in 1500 German hospitals for the period 1995‐2001. Capkun et al examined 2002‐2006 patient panel data from 142 Austrian hospitals and found that increased specialization resulted in shorter patient lengths of stay. Finally, Lindlbauer and Schreyögg analyzed 1239 German acute‐care hospitals for the years 2000‐2011, used different measures of hospital specialization (ie, Herfindahl‐Hirschman index [HHI], Gini index, and Distance index), and found that specialization produced effects on hospital efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…positive association of specialization with efficiency. Both Atella et al 35 and Herwartz and Strumann, 3 With respect to quality of care, finally, a series of studies have shown that hospitals with greater service-specific volumes, particularly for surgical procedures, tend to experience better outcomes (eg, other studies 33,[39][40][41][42][43][44][45][46][47][48] ). For example, Cram et al 46 compared patient outcomes for coronary surgeries between general hospitals and speciality cardiac hospitals, finding evidence of lower mortality rates in the latter.…”
mentioning
confidence: 99%
“…Al-Shammari,1999;Capkun et al, 2012;Gemmel and van Dierdonck, 1999;Gorunescu et al, 2002;Haraden and Resar, 2004;Longo and Masella, 2002;Proudlove and Boaden, 2005;Sarkis and Talluri, 2002). What appears to be required are IT enabled systems that can be used at ward level to support inpatient placement, medical care and then discharge with the additional benefits of 751 Innovations in inpatient flow and bed management providing hospital staff (ward clerks, nurses, clinicians and hospital managers) with the necessary information to assess in a timely manner performance measures based on the ward or department activity.…”
Section: Introductionmentioning
confidence: 99%